Acceptance Threshold: A Bidimensional Research Method for User-Oriented Quality Evaluation Studies. (21st July 2008) - Jumisko-Pyykkö, S.; Malamal Vadakital, V. K.; Hannuksela, M. M.
Abstract : Subjective quality evaluation is widely used to optimize system performance as a part of end-products. It is often desirable to know whether a certain system performance is acceptable, that is, whether the system reaches the minimum level to satisfy user expectations and needs. The goal of this paper is to examine research methods for assessing overall acceptance of quality in subjective quality evaluation methods. We conducted three experiments to develop our methodology and test its validity under heterogeneous stimuli in the context of mobile television. The first experiment examined the possibilities of using a simplified continuous assessment method for assessing overall acceptability. The second experiment explored the boundary between acceptable and unacceptable quality when the stimuli had clearly detectable differences. The third experiment compared the perceived quality impacts of small differences between the stimuli close to the threshold of acceptability. On the basis of our results, we recommend using a bidimensional retrospective measure combining acceptance and satisfaction in consumer-/user-oriented quality evaluation experiments.